2018
DOI: 10.4142/jvs.2018.19.2.309
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hepatitis E virus genotypes 3 and 4 in pig farms in Korea

Abstract: Zoonotic transmission of hepatitis E virus (HEV) is mostly mediated by HEV-3 and HEV-4 genotypes, and domestic pigs are an important reservoir of these genotypes. A survey of 14 pig farms in Korea revealed HEV RNA in 30 of 148 (20.3%) fecal samples. HEV-3a and HEV-4c subtypes were identified in five pig farms (35.7%) and two pig farms (14.3%), respectively. Phylogenetic analysis indicated that the isolated HEV strains were closely related to previously reported zoonotic strains in Korea. The results of the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…KY496215) and swine HEV-3 (GenBank No. MF095679) used in this study were obtained from the stool sample of a rabbit and a pig, respectively, as described in our previous studies [25,26]. The viral titers of both rabbit HEV and swine HEV-3, used to challenge rabbits, were adjusted to 10 6 genomic equivalent (GE) copy number/mL in 4% bovine albumin solution.…”
Section: Experimental Animals and Virusesmentioning
confidence: 99%
“…KY496215) and swine HEV-3 (GenBank No. MF095679) used in this study were obtained from the stool sample of a rabbit and a pig, respectively, as described in our previous studies [25,26]. The viral titers of both rabbit HEV and swine HEV-3, used to challenge rabbits, were adjusted to 10 6 genomic equivalent (GE) copy number/mL in 4% bovine albumin solution.…”
Section: Experimental Animals and Virusesmentioning
confidence: 99%
“…In this study, we found both HEV-3 and HEV-4 in porcine livers sold at grocery markets in Korea. In a previous study, we detected both HEV-3 and HEV-4 in the fecal samples of growing pigs [14]. These results indicate that many pig populations reared in Korea may be infected with zoonotic HEV-3 and HEV-4.…”
mentioning
confidence: 55%
“…Recently, zoonotic infection by HEV-7 was reported in a patient who had consumed camel milk [9]. HEV-3 and HEV-4 have been identified in the fecal and liver samples of pigs in several countries such as Korea [10][11][12][13][14]. Particularly, HEV-3 and HEV-4 were detected in the serum samples of blood donors and patients with acute cryptogenic hepatitis in Korea [15,16].…”
mentioning
confidence: 99%
“…Hepatitis E virus is a zoonotic pathogen with pigs and wild boars serving as natural reservoirs, especially for zoonotic genotypes HEV‐3 and HEV‐4 . Considering the identification of HEV new isolations in disparate animal species, it is obvious that HEV has a broad host range including pigs, rabbits, cats, dogs, horses, rats, cows, sheep, goats and ferrets .…”
Section: Discussionmentioning
confidence: 99%